Preoperative prediction of Bleeding Independently associated with Mortality after noncardiac Surgery (BIMS): an international prospective cohort study. (January 2021) - Roshanov, Pavel S.; Guyatt, Gordon H.; Tandon, Vikas; Borges, Flavia K.; Lamy, Andre; Whitlock, Richard; Biccard, Bruce M.; Szczeklik, Wojciech; Panju, Mohamed; Spence, Jessica; Garg, Amit X.; McGillion, Michael; et al.
Abstract: Background: Diagnostic criteria for Bleeding Independently associated with Mortality after noncardiac Surgery (BIMS) have been defined as bleeding that leads to a postoperative haemoglobin <70 g L −1, leads to blood transfusion, or is judged to be the direct cause of death. Preoperative prediction guides for BIMS can facilitate informed consent and planning of perioperative care. Methods: In a prospective cohort study of 16 079 participants aged ≥45 yr having inpatient noncardiac surgery at 12 academic hospitals in eight countries between 2007 and 2011, 17.3% (2782) experienced BIMS. An electronic risk calculator for BIMS was developed and internally validated by logistic regression with bootstrapping, and further simplified to a risk index. Decision curve analysis assessed the potential utility of each prediction guide compared with a strategy of identifying risk of BIMS based on preoperative haemoglobin <120 g L −1 . Results: With information about the type of surgery, preoperative haemoglobin, age, sex, functional status, kidney function, history of high-risk coronary artery disease, and active cancer, the risk calculator accurately predicted BIMS (bias-corrected C-statistic, 0.84; 95% confidence interval, 0.837–0.852). A simplified index based on preoperative haemoglobin <120 g L −1, open surgery, and high-risk surgery also predicted BIMS, but less accurately (C-statistic, 0.787; 95% confidence interval, 0.779–0.796). Both prediction guides could improve decision making compared with knowledge of haemoglobin <120 g L −1 alone. Conclusions: BIMS, defined as bleeding that leads to a postoperative haemoglobin <70 g L −1, leads to blood transfusion, or that is judged to be the direct cause of death, can be predicted by a simple risk index before surgery. Clinical trial registration: NCT00512109.